Systematic review with network meta‐analysis: comparative efficacy and safety of budesonide and mesalazine (mesalamine) for Crohn's disease. Issue 11 (13th April 2015) - Moja, L.; Danese, S.; Fiorino, G.; Del Giovane, C.; Bonovas, S.
Summary Background Budesonide and mesalazine (mesalamine) are commonly used in the medical management of patients with mild to moderate Crohn's disease. Aim To assess their comparative efficacy and harm using the methodology of network meta‐analysis. Methods A comprehensive search of Medline, Embase, the Cochrane Library and ClinicalTrials.gov, through October 2014, was performed to identify randomised controlled trials (RCTs) that recruited adult patients with active or quiescent Crohn's disease, and compared budesonide or mesalazine with placebo, or against each other, or different dosing strategies of one drug. Results Twenty‐five RCTs were combined using Bayesian network meta‐analysis. Budesonide 9 mg/day, or at higher doses (15 or 18 mg/day), was shown superior to placebo for induction of remission [odds ratio (OR), 2.93; 95% credible interval (CrI), 1.52–5.39, and OR, 3.28; CrI, 1.46–7.55 respectively] and ranks at the top of the hierarchy of the competing treatments. For maintenance of remission, budesonide 6 mg/day demonstrated superiority over placebo (OR, 1.69; CrI, 1.05–2.75), being also at the best ranking position among all compared treatment strategies. No other comparisons (i.e. different doses of mesalazine vs. placebo or budesonide, for induction or maintenance of remission) reached significance. The occurrence of withdrawals due to adverse events was not shown different between budesonide, mesalazine and placebo, in both the induction and maintenance phases. Conclusions Budesonide, at the doses of 9 mg/day, or higher, for induction of remission in active mild or moderate Crohn's disease, and at 6 mg/day for maintenance of remission, appears to be the best treatment choice.